Accommodating individual learning styles - Abney, Mark (New Jersey : Instructivision, 1991)
This video programs designed to increase teachers' knowledge about new research, discoveries, and methods for improving the quality of education
Executive producer, Jay Comras ; editor, Andrew Abbot
Keywords: Learning; Study, Method of; Study skills